Hubungan Otitis Media Akut Dengan Riwayat Infeksi Saluran Pernapasan Atas Pada Anak - Lidya Angelina Purba; Mukhlis Imanto; Dian Isti angraini (Medula, 2021)
Children are very susceptible to Acute Otitis Media (AOM) because the anatomical shape of the eustachian tube is shorter, more flexible and more horizontal than adult. Two thirds of all children have an episode of acute otitis media in the first 3 years of life. Upper Respiratory Tract Infection (ARI) is one of the most common risk factors for causing acute otitis media (AOM) in children. This is because the inflammatory process that occurs in ARI causes damage to mucocilia, goblet cells, and mucus glands in the epithelium of the nasopharynx and middle ear. Children aged under 5 years will usually experience upper respiratory tract infections of two to seven episodes per year. Children who have frequent episodes of ARI are more likely to experience episodes of AOM. his is also in line with repeated episodes of ARI against the risk of AOM recurrence. Recurrent ARI is an ARI that occurs at least four times a year. Therefore, the diagnosis and management of ARI in children as early as possible must be done properly, so that the incidence of ARI in children does not progress to AOM. The causes of otitis media are multifactorial, the anatomical variation of the eutachian tube, and the invasive ability of the pathogen compared to the human's immune system. The diagnosis of otitis media can be confirmed by fulfilling 3 criteria: sudden appearance of the disease, found signs of effusion (known fluid) in the middle ear, found signs of middle ear inflammation.